2021
DOI: 10.1155/2021/5587340
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of AMPK Prevents Diabetes‐Induced Photoreceptor Cell Degeneration

Abstract: Diabetic retinopathy (DR) is a kind of severe retinal neurodegeneration. The advanced glycation end products (AGEs) affect autophagy, and mitochondrial function is involved in DR. Adenosine-activated protein kinase (AMPK) is an important metabolic sensor that can regulate energy homeostasis in cells. However, the effect of AMPK in DR is still not fully understood. In this study, we investigated the effect of AMPK on diabetes-induced photoreceptor cell degeneration. In vivo, a diabetic mouse model was establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…Specifically, AMP first stimulates the phosphorylation of Thr172 by directly activating upstream kinases (Kim et al, 2020). Thr172 can be phosphorylated by several different upstream kinases, which establishes the main mechanism by which AMPK activity is regulated in the short term (Song et al, 2021). Different studies have suggested that LBK1 (liver kinase B1) kinase and MAPKKK family member TAK/MAP3K7 (transforming growth factor beta-activated kinase 1/mitogen-activated kinase 7) can respond to various signals by phosphorylating Thr172 (Fritzen et al, 2016).…”
Section: Ampk: Structures and Activation Mechanismmentioning
confidence: 99%
“…Specifically, AMP first stimulates the phosphorylation of Thr172 by directly activating upstream kinases (Kim et al, 2020). Thr172 can be phosphorylated by several different upstream kinases, which establishes the main mechanism by which AMPK activity is regulated in the short term (Song et al, 2021). Different studies have suggested that LBK1 (liver kinase B1) kinase and MAPKKK family member TAK/MAP3K7 (transforming growth factor beta-activated kinase 1/mitogen-activated kinase 7) can respond to various signals by phosphorylating Thr172 (Fritzen et al, 2016).…”
Section: Ampk: Structures and Activation Mechanismmentioning
confidence: 99%
“…The two types of photoreceptor cells are rod cells, which contain rhodopsin that facilitates vision at night, and cone cells, which contain a cone pigment and are sensitive to high light. In hyperglycemia, rhodopsin expression decreases, and rod cells are more sensitive to hyperglycemia ( Yang M. et al, 2021 ; Song et al, 2021 ).…”
Section: Involved Cellsmentioning
confidence: 99%
“…It has been reported that the AMPK signaling pathway is involved in the etiopathogenesis of many ocular diseases, including DR (30). Song et al demonstrated that stimulation of AMPK signaling pathway attenuate diabetes-induced photoreceptor degeneration through regulation of autophagy and mitochondrial function (31). AMPK phosphorylation is required in the regulation of HMGB1 induced by Epac1 in the diabetic retinal vasculature (32).…”
Section: Discussionmentioning
confidence: 99%